The Efficiency of Sovereign Debt Markets in the EMU: Truth or Mistruth? - Waszkiewicz, Grzegorz (Olsztyn Economic Journal, 2020)
Ever since the last financial crisis, the efficiency of financial markets has been widely challenged. On the basis of sovereign debt markets in the European Monetary Union (EMU), we tried to contrast some reservations about the market efficiency existing in the literature with findings coming from our empirical analysis of weak-form efficiency. To do so, we first outlined the crux of the efficient market hypothesis. Secondly, we show the main reservations in relation to this concept. Then, after a brief review of outcomes from contributions in this area, we conducted a three-stage empirical procedure that Worthington and Higgs (2006) as well as Borges (2009) had employed to stock markets analysis. Then, the results were evaluated and conclusions were drawn. To sum up, we did confirm the weak-form efficiency on examined sovereign debt markets from the EMU. That suggests that a random process plays a key role in shaping bond yields. Finally, neither theoretical nor practical reservations deflate the weak-form efficiency in the public debt markets of the EMU.